No Accumulation of Transposable Elements in Asexual Arthropods - Bast, Jens (Mol Biol Evol, 2016)
Transposable elements (TEs) and other repetitive DNA can accumulate in the absence of recombination, a process contributing to the degeneration of Y-chromosomes and other nonrecombining genome portions. A similar accumulation of repetitive DNA is expected for asexually reproducing species, given their entire genome is effectively nonrecombining. We tested this expectation by comparing the whole-genome TE loads of five asexual arthropod lineages and their sexual relatives, including asexual and sexual lineages of crustaceans (Daphnia water fleas), insects (Leptopilina wasps), and mites (Oribatida). Surprisingly, there was no evidence for increased TE load in genomes of asexual as compared to sexual lineages, neither for all classes of repetitive elements combined nor for specific TE families. Our study therefore suggests that nonrecombining genomes do not accumulate TEs like nonrecombining genomic regions of sexual lineages. Even if a slight but undetected increase of TEs were caused by asexual reproduction, it appears to be negligible compared to variance between species caused by processes unrelated to reproductive mode. It remains to be determined if molecular mechanisms underlying genome regulation in asexuals hamper TE activity. Alternatively, the differences in TE dynamics between nonrecombining genomes in asexual lineages versus nonrecombining genome portions in sexual species might stem from selection for benign TEs in asexual lineages because of the lack of genetic conflict between TEs and their hosts and/or because asexual lineages may only arise from sexual ancestors with particularly low TE loads.